Formirovanie I Razvitie Kognitivnyx Sposobnostey Studentov V Obuchenii Injenernoy Grafiki (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Cognitive ability is the ability of a person to perceive, understand, process and use information for decision-making, decision-making and adaptation to new situations. Ona vklyuchaet v sebya takie aspekty, kak vnimanie, pamyat, myshlenie, vospriyatie, rech, reshenie problem, logicaleskoe myshlenie i t. d. Cognitive abilities play an important role in our ability to learn, adapt and function in everyday life [1].